2019
DOI: 10.1111/pbi.13126
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study of six quality traits reveals the association of the TaRPP13L1 gene with flour colour in Chinese bread wheat

Abstract: Summary Flour colour, kernel hardness, grain protein content and wet gluten content are important quality properties that determine end use in bread wheat. Here, a wheat 90K genotyping assay was used for a genome‐wide association study (GWAS) of the six quality‐related traits in Chinese wheat cultivars in eight environments over four years. A total of 846 significant single nucleotide polymorphisms (SNPs) were identified, explaining approximately 30% of the phenotypic variation on average, and 103 multienviron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 59 publications
0
48
0
Order By: Relevance
“…Three panels composed of Chinese common wheat have been genotyped by different wheat SNP arrays in our previous studies (Chen et al , 2019; Sun et al , 2017; Yang et al , 2019). Panel_I, containing 163 Chinese cultivars, was characterized by the Wheat 90K SNP array (Sun et al , 2017), and analysis indicated that the heterozygosity of cultivars characterized by the Wheat 90K SNP array in Panel_I was 28.67%.…”
Section: Comparison Of the Seven Popular Wheat Arraysmentioning
confidence: 99%
“…Three panels composed of Chinese common wheat have been genotyped by different wheat SNP arrays in our previous studies (Chen et al , 2019; Sun et al , 2017; Yang et al , 2019). Panel_I, containing 163 Chinese cultivars, was characterized by the Wheat 90K SNP array (Sun et al , 2017), and analysis indicated that the heterozygosity of cultivars characterized by the Wheat 90K SNP array in Panel_I was 28.67%.…”
Section: Comparison Of the Seven Popular Wheat Arraysmentioning
confidence: 99%
“…High-density genotyping platforms for wheat, such as 90K iSelect [19] and 660K Axiom arrays (http://wheat.pw.usda.gov/ggpages/topics/Wheat660_SNP_array_developed_by_ CAAS.pdf), enable us to perform genome-wide association studies (GWASs) using a set of germplasms or advanced breeding lines. GWASs of wheat quality traits have drastically emerged within the last five years and revealed many significant marker-trait associations (MTAs) across the wheat genome [20][21][22][23][24][25]. These MTAs would be useful for improving wheat quality.…”
Section: Introductionmentioning
confidence: 99%
“…In other plant studies, it has been found that RPP13 gene homologs take part in tomato resistance to yellow leaf curl virus (Chen et al., 2013), grape powdery mildew (Han et al., 2016) and regulation of sugarcane leaf shedding (Li et al., 2016). Interestingly, TaRPP13L1 gene also involves in regulating wheat flour colour (Chen et al., 2019). Overall, RPP13 plays a key role in resistance to fungi, bacteria and viruses, and contributes to plant growth and development; however, its contribution to wheat powdery mildew resistance remains limited.…”
Section: Introductionmentioning
confidence: 99%